2019
DOI: 10.1007/s10899-019-09892-7
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Gambling, Gambling Expenditure and Gambling–Related Harms in Finland, 2011–2017

Abstract: Existing literature on recent trends in adolescent gambling is scarce. The rapidly changing landscape of gambling, together with the generally applied legal age limits, calls for the continuous monitoring of gambling also among the adolescent population. In Finland, the legal gambling age is 18. We examined changes in adolescents’ gambling, gambling expenditure and gambling–related harms from 2011 to 2017. Comparable cross-sectional biennial survey data were collected in 2011, 2013, 2015 and 2017 among 12–18-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…2 81 Unsurprisingly, 18-year-olds who were not targeted by the age restriction increase showed no significant changes in gambling activity. 81 However, underaged gambling was still occurring in about 13% of their sample. 2 One study found decreases in lottery games and slot machine gambling for the 15-to 17-year-old age group and the 18-to 19-year-old age group, three years post legislation change.…”
Section: Raising the Age Limitmentioning
confidence: 97%
See 2 more Smart Citations
“…2 81 Unsurprisingly, 18-year-olds who were not targeted by the age restriction increase showed no significant changes in gambling activity. 81 However, underaged gambling was still occurring in about 13% of their sample. 2 One study found decreases in lottery games and slot machine gambling for the 15-to 17-year-old age group and the 18-to 19-year-old age group, three years post legislation change.…”
Section: Raising the Age Limitmentioning
confidence: 97%
“…53 Four Finnish studies that examined the effects of raising the legal age restrictions to gamble were found in the literature. 1,2,81,82 This section will discuss the findings and recommendations from these studies. The age restriction to gamble in Finland was raised from 15 to 18 years old with an interest in protecting youth from gambling-related harms in 2010.…”
Section: Raising the Age Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that verbal abuse was most commonly males towards their mother, but found no difference in cases of physical abuse between genders. McCarthy et al 65 found that women were more likely to report mental health comorbidity than males, however causality was not discussed, and Raisamo et al 66 found that while the most common harm was guilt for both genders, the second was disrupted schoolwork for females and con ict with friends for males.…”
Section: Gendermentioning
confidence: 99%
“…They also found that verbal abuse was most commonly males towards their mother, but found no difference in cases of physical abuse between genders. McCarthy et al 62 found that women were more likely to report mental health comorbidity than males, however causality is not discussed, and Raisamo et al 63 found that although the most common harm was guilt for both genders, the second most common was disrupted schoolwork for females and con ict with friends for males.…”
Section: Gendermentioning
confidence: 99%